Intravascular Papillary Endothelial Hyperplasia: Diagnostic Sequence and Literature Review of an Orofacial Lesion - Mahima V. Guledgud; Karthikeya Patil; Degala Saikrishna; Abhishek Madhavan; Tejesh Yelamali (Case Reports in Dentistry)
Intravascular papillary endothelial hyperplasia or Masson’s tumor is a rare reactive disease of vascular origin characterized by exuberant proliferation of endothelial cells notably occurring within blood vessels of head, neck, and extremities. The importance of this entity is its ability to mimic a variety of diseases both benign and malignant in the orofacial region. Here, we present a case of Masson’s tumor within the masseter muscle in a 40-year-old female with emphasis on the sequential investigative procedures performed to diagnose this entity.